Two-stage robust planning method for distribution network energy storage based on load forecasting - Yuan, Minghan; Zhang, Hua; Ji, Kunhua; Liu, Yangyang; Tang, Xiao; Tao, Biao; Li, Zichen; Mi, Yang (Frontiers in Energy Research, 2024)
A two-stage robust planning method for energy storage in distribution networks based on load prediction is proposed to address the uncertainty of active load in energy storage planning. Firstly, considering the uncertainty of active load, a short-term load forecasting model combining mutual information method and BILSTM is established based on k-means++clustering. Secondly, based on the results of load forecasting, a comprehensive norm constrained uncertainty set is constructed, and a two-stage robust model for distribution network energy storage planning is established. The first stage aims to minimize the annual investment cost of the energy storage system, while the second stage aims to minimize the daily operating cost of the distribution network. At the same time, a second-order cone relaxation transformation model with non convex constraints is introduced to ultimately achieve the optimal economy of the distribution network in energy storage planning. Finally, the effectiveness of the proposed method and model is validated on the IEEE33 node distribution network model using the MATLAB platform.